2020
DOI: 10.4317/medoral.23305
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the immunohistochemical detection of epithelial-mesenchymal transition biomarkers in oral epithelial dysplasia: A systematic review

Abstract: Background: Oral potentially malignant disorders (OPMDs) comprise a range of clinical-pathological alterations that are frequently characterized as architectural and cytological derangements upon histological analysis. Epithelial-mesenchymal transition (EMT) has been proposed as a critical mechanism for the acquisition of the malignant phenotype in neoplastic epithelial processes. This study aims to systematically review the current findings on the immunohistochemical expression of epithelial-mesenchymal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…After duplicate elimination, 3924 records were considered potentially eligible and screened according to titles and abstracts, leaving a sample of 92 studies for full text evaluation. Finally, 85 studies meeting all eligibility criteria were included for critical analysis and evidence synthesis in our scoping review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicate elimination, 3924 records were considered potentially eligible and screened according to titles and abstracts, leaving a sample of 92 studies for full text evaluation. Finally, 85 studies meeting all eligibility criteria were included for critical analysis and evidence synthesis in our scoping review [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis [ 59 ] studied the relative frequency of CDH1 gene methylation—encoding E-cadherin—in oral cancer, demonstrating that this epigenetic mechanism may be involved in the loss of expression of this relevant adhesion molecule. One line of evidence points to the scarcity of existing studies on transcription factors involved in EMT [ 26 , 35 , 39 , 40 , 75 ]. In this regard, only a systematic review and meta-analysis [ 75 ], performed on a small number of primary level studies, showed that Twist overexpression did not influence the survival of oral cancer patients, although these results are not very robust and perhaps a larger sample size may reveal the actual prognostic influence of this marker.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant fact of the EMT process is its reversible character, so that these cells can re-express E-cadherin and recover both their inter-cellular junctions and their polygonal epithelial morphology, which seems necessary for metastatic colonies to successfully implant and reach the category of macrometastasis [ 179 ]. The EMT phenomenon is governed by the actions of some transcription factors (Snal, Slug, Twist, zab1/2) that activate genes involved in the process [ 180 , 181 , 182 , 183 , 184 ], especially in the loss of E-cadherin [ 185 , 186 , 187 ]. An interesting observation refers to the fact that the EMT phenomenon is not homogeneous in a tumor, appearing more clearly in the peripheral areas, just in the invasion zones, which suggests that perhaps some stromal stimuli or a factor from the peritumoral inflammatory infiltrate may constitute driving forces of EMT [ 188 , 189 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Previous studies indicated that these EMT markers may be involved in the malignant transformation of patients with oral dysplasia. 23 Although the EMT process promoted by lncRNAs has been proposed as a critical mechanism for the acquisition of the malignant phenotype in OSCC, [24][25][26] the dysregulation of EMT-related proteins by lncRNAs in OPMD was unknown. In the gain-of-function studies on LOLA1 in Leuk1, the reduction in E-cadherin expression and upregulation of Vimentin and N-cadherin expression F I G U R E 6 Schematic for the regulatory relationship among LOLA1, AKT, and GSK-3β in OL.…”
Section: Discussionmentioning
confidence: 99%